2000
DOI: 10.1038/sj.leu.2401839
|View full text |Cite
|
Sign up to set email alerts
|

High-dose cytosine arabinoside and daunorubicin induction therapy for adult patients with de novo non M3 acute myelogenous leukemia: impact of cytogenetics on achieving a complete remission

Abstract: Cytogenetic abnormalities are used to define prognostic subgroups of acute myelogenous leukemia (AML) with respect to achieving complete remission (CR) and remaining disease free. These prognostic groups for obtaining CR were based on an induction regimen mainly using standard dose cytosine arabinoside (Ara-C) + daunorubicin (DNR). We have reviewed our experience with 122 adult patients with de novo non-M3 AML who were treated with high-dose (HD) Ara-C 3 g/m 2 given over 3 h every 12 h for a total of eight dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Although nonspecific in their effects, these regimens have significantly increased the survival of AML patients. [3][4][5] Recently, more targeted therapy has been developed. Treatment of acute promyelocytic leukemia (APL) patients with trans-retinoic acid (tRA) results in the differentiation of the leukemic cells, with 90% of the patients achieving a complete remission.…”
Section: Introductionmentioning
confidence: 99%
“…Although nonspecific in their effects, these regimens have significantly increased the survival of AML patients. [3][4][5] Recently, more targeted therapy has been developed. Treatment of acute promyelocytic leukemia (APL) patients with trans-retinoic acid (tRA) results in the differentiation of the leukemic cells, with 90% of the patients achieving a complete remission.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, two phase II trials have also used high dose cytarabine during induction in an effort to improve CR rates. Stein et al [20] at the City of Hope used cytarabine 3 g/m 2 bid for eight doses followed by daunorubicin 60 mg/m 2 on Days 5 and 6. In this single institution study, CR was seen in 80% of patients including 62% of patients with poor-risk cytogenetics [20].…”
Section: Discussionmentioning
confidence: 99%
“…Stein et al [20] at the City of Hope used cytarabine 3 g/m 2 bid for eight doses followed by daunorubicin 60 mg/m 2 on Days 5 and 6. In this single institution study, CR was seen in 80% of patients including 62% of patients with poor-risk cytogenetics [20]. Mitus et al [12] piloted the 3 1 7 1 3 regimen investigated in this SWOG study.…”
Section: Discussionmentioning
confidence: 99%
“…41 Cytogenetic abnormalities are used to define prognostic subgroups of AML with respect to achieving CR and remaining disease free. The group with favorable cytogenetics benefits more from cytarabine dose escalation in induction therapy (Burnett AK et al Br J Haemtol 1996; 93(Suppl 2): 313; abstract) [59][60][61] and from HDAC in consolidation therapy. 62,63 Jahns et al 64 reported the findings of cell-cycle studies of the blast cells from different cytogenetic risk groups.…”
Section: Discussionmentioning
confidence: 99%